Traction stress in focal adhesions correlates biphasically with actin retrograde flow speed - Gardel, Margaret L.; Sabass, Benedikt; Schwarz, Ulrich S. (The journal of cell biology, 2008)
How focal adhesions (FAs) convert retrograde filamentous actin (F-actin) flow into traction stress on the extracellular matrix to drive cell migration is unknown. Using combined traction force and fluorescent speckle microscopy, we observed a robust biphasic relationship between F-actin speed and traction force. F-actin speed is inversely related to traction stress near the cell edge where FAs are formed and F-actin motion is rapid. In contrast, larger FAs where the F-actin speed is low are marked by a direct relationship between F-actin speed and traction stress. We found that the biphasic switch is determined by a threshold F-actin speed of 8-10 nm/s, independent of changes in FA protein density, age, stress magnitude, assembly/disassembly status, or subcellular position induced by pleiotropic perturbations to Rho family guanosine triphosphatase signaling and myosin II activity. Thus, F-actin speed is a fundamental regulator of traction force at FAs during cell migration.